2020
DOI: 10.14309/ctg.0000000000000161
|View full text |Cite
|
Sign up to set email alerts
|

Double Stenting for Malignant Biliary and Duodenal Obstruction: A Systematic Review and Meta-Analysis

Abstract: INTRODUCTION: Data about the efficacy of palliative double stenting for malignant duodenal and biliary obstruction are limited. METHODS: A systematic literature search was performed to assess the feasibility and optimal method of double stenting for malignant duodenobiliary obstruction compared with surgical double bypass in terms of technical and clinical success, adverse events, reinterventions, and survival. Event rates with 95% confidence intervals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 76 publications
0
8
0
1
Order By: Relevance
“…However, it has recently been substituted by less invasive endoscopic procedures due to its high morbidity and mortality. A recent systematic review and meta-analysis reported that endoscopic double stenting was associated with higher clinical success (97% vs. 86%) and less adverse events (13% vs. 28%), but with a more frequent need for reintervention (21% vs. 10%) compared with double surgical bypass [ 17 ]. Even though endoscopic double stenting has become the standard treatment for combined biliary and duodenal obstruction [ 18 ], minimally invasive surgical procedures such as laparoscopic gastrojejunostomy are still favored in patients with a long life expectancy, due to reports suggesting better long-term outcomes [ 19 , 20 , 21 ].…”
Section: Treatment Options For Combined Malignant Biliary and Duodenal Obstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has recently been substituted by less invasive endoscopic procedures due to its high morbidity and mortality. A recent systematic review and meta-analysis reported that endoscopic double stenting was associated with higher clinical success (97% vs. 86%) and less adverse events (13% vs. 28%), but with a more frequent need for reintervention (21% vs. 10%) compared with double surgical bypass [ 17 ]. Even though endoscopic double stenting has become the standard treatment for combined biliary and duodenal obstruction [ 18 ], minimally invasive surgical procedures such as laparoscopic gastrojejunostomy are still favored in patients with a long life expectancy, due to reports suggesting better long-term outcomes [ 19 , 20 , 21 ].…”
Section: Treatment Options For Combined Malignant Biliary and Duodenal Obstructionmentioning
confidence: 99%
“…In general, the technical success rate was greatly influenced by the biliary drainage method and the proportion of type II obstructions. A systematic review and meta-analysis found that ERCP was associated with similar clinical success and less adverse events (3% vs. 23%) compared to EUS-BD for biliary drainage as part of double stenting [ 17 ]. As a result, ERCP remains the preferred treatment option when transpapillary biliary access is possible.…”
Section: Treatment Options For Combined Malignant Biliary and Duodenal Obstructionmentioning
confidence: 99%
“…92 %. Im Vergleich zur chirurgischen Doppelbypassoperation wurden bei der endoskopischen Intervention weniger Komplikationen beobachtet (13 vs. 28 %), aber Reinterventionen waren deutlich häufiger erforderlich (21 vs. 10 %) [11].…”
Section: Kombinierte Duodenale Und Biliäre Obstruktionunclassified
“…However, hyperplasia is commonly associated with partially‐covered SEMS, which are widely used in EUS‐HGS 12 . Transpapillary stenting is still recommended as the first choice for biliary stenting if feasible due to the low adverse events based on a systematic review and meta‐analysis 13 …”
Section: Introductionmentioning
confidence: 99%
“…12 Transpapillary stenting is still recommended as the first choice for biliary stenting if feasible due to the low adverse events based on a systematic review and meta-analysis. 13 Although several anti-reflux metal stents (ARMS) have been investigated to prevent duodeno-biliary reflux, only Windsock-type ARMS exhibited superiority against conventional CMS. [14][15][16] Recently, a Duckbill-type metal stent (Kawasumi Duckbill Biliary Stent, SB-Kawasumi Laboratories) has been developed and its effectiveness as an ARMS has been reported.…”
Section: Introductionmentioning
confidence: 99%